Changing the rules: Applying a more economic approach to dynamic telecom markets - Jan Krancke; Miguel Vidal; Andreas Fier (International Telecommunications Society (ITS), 2012)
Traditionally, neoclassical economics has been the guiding framework in the development of legislative and regulatory rules in the telecommunication markets. The regulatory perspective has long assumed a static environment. However, telecommunication markets have evolved into extremely dynamic, innovative and technology-driven markets. At the same time, economic theory has moved well beyond simple, static concepts of neo-classical analysis. Inter alia, Schumpeterian Economics, Institutional Economics and modern Industrial Organization provide a broader framework more suitable to analyze modern telecom markets. Drawing on an extended theoretical baseline and on major industry trends, we propose a more comprehensive framework for telecom regulation - the new regulatory pentagon - based on the cornerstones competition, investment and innovation, convergence and platformization, macroeconomics and growth and, lastly, commitment and credibility.
Keywords: 330; Telecommunications; Regulation; Network investments; Platforms; Innovation; Next generation networks